Presentation of Tongue Cancer at a Tertiary Hospital in the Western Region of Saudi Arabia - Almoaidbellah A. Rammal,; Saad M. Al Muhayawi,; Khalid B. Al-Ghamdi,; Samaher A. Ashram,; Rafat S. Sindi, (Journal of King Abdulaziz University: Medical Sciences, 2023)
To describe the presentation of tongue cancer in patients who were followed up at King Abdulaziz University Hospital, and stress on the importance of community programs. A retrospective study conducted on patients diagnosed with tongue cancer at the Department of Otolaryngology and Head and Neck Surgery between 2005 and 2011. Data was collected on demographic and clinical findings with the help of a preformed questionnaire. 24 patients (14 males and 10 females) were studied. The common presenting symptoms were ulcers (58.3%) and masses (41.7%). Seven (29.2%) patients had history of smoking and alcohol consumption in 6 (25.0%) cases. Most patients were diagnosed with advanced disease (41.7 and 37.5% for stages 3 and 4, respectively). For all stages, the minimum age at diagnosis was 31 years, while the maximum age was 79 years. There was no significant difference in age between the patients with respect to the cancer stages (p = 0.895). The most common pathological variant was squamous cell carcinoma (n = 23, 95.8%). In conclusion, most patients had stages 3 and 4 disease at the time of diagnosis. It might be necessary to implement programs aimed at educating the community and healthcare personnel in order to reduce late presentation to hospital.